FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PERAWAT DI UNIT GAWAT DARURAT RSUD DR.H.CHASAN BOESOIRIE TERNATE - Suni, Arsad; Pandawa, Rugaya M; Saleh, Fatma M (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2016)
Abstract : The problem of job stress is not addressed will be able to reduce the level of labor productivity and reflects a poor performance. Many factors play a role as a trigger of workplace stress everyone. If the stress of work is going on a nurse, then the role of which is the nurse characteristics (age, education level, marital status, employment status, type of personality), work environment, and the work itself. Generally, job stress caused by the demands of the job do not match the capabilities and skills of workers, which is often the cause staunch educational factors, personality type, and work environment. This study used analytic method with cross sectional approach, and the sampling technique is done by total sampling 22 responden and chi-square test with significance level α = 5 % (0.05). The analysis showed a significant relationship between work environment factors to the stress of nurses working in the Intensive Care Unit Hospital Dr.H. Chasan Boesoirie Ternate with p = 0.015, no significant relationship between the factors of job stress of nurses with a value of p = 0.574, there is a significant relationship between the level of education and work stress nurse with a value of p = 0.003, there was a significant association between type personality with work stress nurse with a value of p = 0.023, there was no significant relationship between age and job stress of nurses with a value of p = 0.293, there was no significant relationship between marital status with the stress of nurses with a value of p = 0983, no relationship was significant between employment status with the stress of nurses with a value of p = 0562, and the factors most associated with job stress of nurses in the Emergency Unit of Hospital Dr. H. Chasan Boesoirie Ternate is a personality type with Exp (B) 12.093. Therefore, it is expected that the Hospital Dr. H. Chasan Boesoirie Ternate to deregulate (restructuring) tasks and roles with the application of professional nursing practice.